Penilaian kinerja pengolahan limbah cair di konteks pulau kecil: evaluasi multi-aspek Pulau Tidung Besar, Indonesia - Prayoga, Gatot; Yulianto, Gatot; Effendi, Hefni (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2025)
Small islands face unique sustainability challenges in domestic wastewater management (DWM) due to limited resources, confined space, and high ecological vulnerability, yet comprehensive multi-dimensional assessments remain scarce. This study addresses this gap through a multi-aspect assessment of the DWM system on Tidung Besar Island, Indonesia, integrating technical, institutional, environmental, and social dimensions in a densely populated tourism-based small island. An exploratory-descriptive approach was employed, combining field observations, stakeholder interviews, questionnaires, and secondary data analysis from March 2024 to August 2025. Data were analyzed through triangulation methods, descriptive statistics, and qualitative synthesis. The study reveals a critical paradox that despite strong community acceptance and established infrastructure comprising four wastewater treatment plants serving 831 house connections, the system faces severe environmental challenge. Ammonia and total coliform exceed quality standards by up to 163 and 137 times. Technical challenges include overcapacity in high-demand zones, equipment failures, and incomplete service coverage, while institutional monitoring remains weak. Socially, most residents lack wastewater knowledge yet report high satisfaction based on visible improvements. This reveals that community acceptance alone cannot serve as a reliable indicator of system success. The study also demonstrates that small island wastewater management requires integrated solutions addressing interconnected challenge across all dimensions simultaneously.